ANALISIS FAKTOR PENYEBAB KESULITAN BELAJAR MATEMATIKA MATERI PERKALIAN DAN PEMBAGIAN PADA SISWA KELAS IV DI SD NEGERI 02 KUPU BREBES - Naufal, Hanis Zamzami; Bara Saputro, Hengkang (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
The background of this research is learning the arithmetic operations of multiplication and division in class IV. It can be seen that most students complain when the teacher invites students to study mathematics. Students seemed less or less enthusiastic, lazing around, some even talked to their friends and didn't pay attention to the teacher's explanation. Learning outcomes in class IV of SD Negeri 02 Kupu Brebes are still relatively low or do not meet the minimum completeness criteria (KKM). This research aims to determine the types of difficulties in learning the arithmetic operations of multiplication and division as well as the inhibiting factors in learning the arithmetic operations of multiplication and division experienced by fourth grade students at SD Negeri 02 Kupu Brebes. The type of research used is qualitative research. The subjects of this research were the class teacher and 4 class IV students due to the teacher's confession during the pre-interview and the teacher was more involved during teaching and learning activities and discussions. The items taken are the types of difficulties in learning the arithmetic operations of multiplication and division, as well as factors that hinder the learning of arithmetic, multiplication and distribution operations. Data collection techniques include interviews and documentation. The results of the research carried out were the types of difficulties in learning multiplication and division arithmetic operations experienced by students, namely difficulties in distinguishing symbols, difficulties in solving problems of multiplication and division arithmetic operations, weaknesses in understanding the concept of numbers, difficulty distinguishing the relationship between the concepts of multiplication arithmetic operations. and division numbers, as well as factors in learning the multiplication and division arithmetic operations experienced by students, namely the student's physical condition, the spiritual condition within the student, the parents' attitude towards the student, the student's home or family environment, the teacher's attitude at school. Keywords: Learning Difficulties, multiplication, division, elementary school